(untitled) - Persico, Enrico (Englewood Cliffs, NJ., 1950)
Historical development and experimental bases. The atomic odel, energy quanta and light quanta. energy levels, quantum mechanics, Wave mechanics of a particle. Mathematical introduction, probabilistic statement of atomic problems.
Keywords: Atoms,Wave mechanics,Nguyên tử,Cơ học sóng